Pengembangan Game Edukasi Teraven of Majapahit untuk Mendukung Kemampuan Literasi Numerasi Siswa SMA - Ermawan, Redita Putri; Anjariyah, Deka; Feriyanto, Feriyanto (YASIN, 2025)
Mathematics instruction at SMA Negeri 1 Mojosari, particularly in Grade X trigonometry, remains dominated by conventional media such as PowerPoint and videos, resulting in low student engagement and suboptimal numeracy literacy outcomes. Observations and interviews revealed that approximately 75% of students had not reached the Minimum Mastery Criteria (KKTP) score of 75 in trigonometry quizzes. This study aims to develop the educational game TERAVEN of Majapahit using Construct 2 as a learning medium to enhance high school students’ numeracy literacy, while also assessing its feasibility and student response. The research method employed was Research and Development (R&D) using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. Instruments included validation questionnaires by media and content experts, student response questionnaires, and numeracy literacy tests. Validation results showed scores of 89.9% from the media expert and 94% from the content expert, both categorized as "highly valid." Small group trials yielded a practicality score of 79.5%, and large group trials 69.94%, both falling under the “practical” category. The numeracy literacy test indicated an 80% mastery rate, categorized as “high.” These findings confirm that TERAVEN of Majapahit is a valid, practical, and effective medium for mathematics learning. The study also underscores the importance of integrating interactive digital media rooted in local wisdom to create engaging and contextual learning experiences, especially for trigonometry—a topic often perceived as difficult.